UNVEILING HANNA SCHMITZ: A SOCIOCULTURAL ANALYSIS OF MORALITY, GUILT, AND MEMORY IN BERNHARD SCHLINK'S THE READER - Bakr, Mahir Ahmed; Abdul, Zanyar Kareem; Alipour, Ahdiyeah (Universitas Islam Sumatera Utara (UISU), 2024)
This paper, titled